Coexistence of mitochondrial DNA and β myosin heavy chain mutations in hypertrophic cardiomyopathy with late congestive heart failure. Issue 6 (1st December 1998) - Arbustini, E; Fasani, R; Morbini, P; Diegoli, M; Grasso, M; Dal Bello, B; Marangoni, E; Banfi, P; Banchieri, N; Bellini, O; Comi, G; Narula, J; et al.
Abstract : Objective: To investigate the possible coexistence of mitochondrial DNA (mtDNA) mutations in patients with β myosin heavy chain (βMHC) linked hypertrophic cardiomyopathy (HCM) who develop congestive heart failure. Design: Molecular analysis of βMHC and mtDNA gene defects in patients with HCM. Setting: Cardiovascular molecular diagnostic and heart transplantation reference centre in north Italy. Patients: Four patients with HCM who underwent heart transplantation for end stage heart failure, and after pedigree analysis of 60 relatives, eight additional affected patients and 27 unaffected relatives. A total of 111 unrelated healthy adult volunteers served as controls. Disease controls included an additional 27 patients with HCM and 102 with dilated cardiomyopathy. Intervention: Molecular analysis of DNA from myocardial and skeletal muscle tissue and from peripheral blood specimens. Main outcome measures: Screening for mutations in βMHC (exons 3–23) and mtDNA tRNA (n = 22) genes with denaturing gradient gel electrophoresis or single strand conformational polymorphism followed by automated DNA sequencing. Results: One proband (kindred A) (plus seven affected relatives) had arginine 249 glutamine (Arg249Gln) βMHC and heteroplasmic mtDNA tRNAIle A4300G mutations. Another unrelated patient (kindred B) with sporadic HCM had identical mutations. The remaining two patients (kindred C), a mother and son, had a novel βMHC mutation (lysine 450 glutamic acid) (Lys450Glu) and a heteroplasmic missense (T9957C, phenylalanine (Phe)–>leucine (Leu)) mtDNA mutation in subunit III of the cytochrome C oxidase gene. The amount of mutant mtDNA was higher in the myocardium than in skeletal muscle or peripheral blood and in affected patients than in asymptomatic relatives. Mutations were absent in the controls. Pathological and biochemical characteristics of patients with mutations Arg249Gln plus A4300G (kindreds A and B) were identical, but different from those of the two patients with Lys450Glu plus T9957C(Phe–>Leu) mutations (kindred C). Cytochrome C oxidase activity and histoenzymatic staining were severely decreased in the two patients in kindreds A and B, but were unaffected in the two in kindred C. Conclusions: βMHC gene and mtDNA mutations may coexist in patients with HCM and end stage congestive heart failure. Although βMHC gene mutations seem to be the true determinants of HCM, both mtDNA mutations in these patients have known prerequisites for pathogenicity. Coexistence of other genetic abnormalities in βMHC linked HCM, such as mtDNA mutations, may contribute to variable phenotypic expression and explain the heterogeneous behaviour of HCM.